Efficacy of improvised portable electrolysis console on students’ academic achievement in physics - Abdukarim, Abdulsalam; Babajide, Veronica Folasade T.; Raheem, Isiaka Ayobi (Papanda Publisher, 2025)
The dearth of instructional materials in teaching key concepts in Physics such as Electrolysis in Nigerian schools is rather disparaging to productive and effective teaching and learning. As such, improvising to mitigate this lack of instructional materials becomes an imperative intervention. This study investigated the efficacy of an improvised portable electrolysis console on the academic achievement of physics students in Lagos State senior secondary schools. The Improvised Portable Electrolysis Console, IPEC, is a PCB (Printable Circuit Board) designed semi-automatic electronic instructional material which allows teachers and learners to physically carry out electrolysis experiments, (i.e. Verification of Faraday’s laws of electrolysis, electroplating, and de- rusting). The pretest-posttest control group non-randomized quasi-experimental research design was employed in the study. A total of 143 students, (70 male and 73 female) from 4 co-educational public senior secondary schools in Lagos State, Nigeria constituted the sample. A validated research instrument-Electrolysis Students Written Achievement Test (ESWAT), (reliability coefficient; r = 0.75) was used in data collection. Two research questions were answered, and two research hypotheses were both tested at a 0.05 level of significance. The data gathered were analyzed using descriptive statistics, ANCOVA and independent samples t–test. The results showed that the learners’ taught using the IPEC intervention had better academic achievement than their counterparts who were not exposed to the use of the IPEC. Also, there was no statistically significant gender disparity in the achievement of students exposed to the use of IPEC, showing that the achievement of both genders of learners was influenced equally, i.e., the IPEC intervention has no gender disparity. The study therefore recommended the use of Improvised Portable Electrolysis Console for the teaching and learning of electrolysis in physics.